Time's arrows today : recent physical and philosophical work on the direction of time - Savitt, Steven F. (Cambridge unievrsity press, 1995)
While experience tells us that time flows from the past to the present and into the future, a number of philosophical and physical objections exist to this commonsense view of dynamic time. In this book, researchers from both physics and philosophy attempt to answer these issues in an interesting, yet rigorous way.
Includes bibliographical references and index.
Keywords: Causality (Physics).; Space and time